1992
DOI: 10.1139/v92-080
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of nitro–nitrite rearrangement of CH3NO2

Abstract: This paper is dedicated to Professor Sigerzi Hzizinc~gc~ otz the occasion of his 65th birthdayROBERTA P. SAXON and MEGUMU YOSHIMINE. Can. J . Chem. 70, 572 (1992). Calculations designed to characterize the transition state and determine the barrier height for rearrangement of nitromethane to methyl nitrite are reported. Structures of CH,NO,, C H 3 0 N 0 , dissociation products, CH3 + NOz and CH,O + NO, and the transition state for nitro-nitrite rearrangement have been optimized at the MCSCF/4-31G level. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 10 publications
(18 reference statements)
8
38
1
Order By: Relevance
“…They confirmed a loose transition state (TS1 in Fig. 2), reported by Mckee [59] and Saxon et al [60] at a large C-N distance just below the C-N dissociation threshold and suggested it could be analogous to the roaming behavior seen in formaldehyde, i.e., roaming isomerization for the CH 3 NO 2 ↔ cis-CH 3 ONO reaction. They reproduced the experimental branching ratio of Ref.…”
Section: Introductionsupporting
confidence: 80%
“…They confirmed a loose transition state (TS1 in Fig. 2), reported by Mckee [59] and Saxon et al [60] at a large C-N distance just below the C-N dissociation threshold and suggested it could be analogous to the roaming behavior seen in formaldehyde, i.e., roaming isomerization for the CH 3 NO 2 ↔ cis-CH 3 ONO reaction. They reproduced the experimental branching ratio of Ref.…”
Section: Introductionsupporting
confidence: 80%
“…The shape of the 10 active orbitals employed is similar to those displayed in Figure 1, which are the natural orbitals (NO) obtained from a CASSCF calculation. Note that, in previous studies, 18,19 only an active space of four-electron-in-four-orbital was used in MCSCF computations.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the latest results 20 substantiated the discrepancy not only between experimental and theoretical analyses but also between theoretical results reported in earlier papers. [13][14][15][16][17][18][19] Nevertheless, the nature of the TS for rearrangement, tight versus loose, has not been examined by an appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Unimolecular rearrangement of nitromethane to methyl nitrite, CH NO EF CH ONO 3 2 3 has been suggested [41] to be competitive with the simple bond fission (R1), but theoretical work [42,43] points to a high energy barrier for the isomerization pathway, making it negligible under conditions of interest. More important are secondary reactions of CH 3 NO 2 with the radical pool [27].…”
Section: ϫ1 ϫ1mentioning
confidence: 99%